Long-term wheel-running and acute 6-h advances alter glucose tolerance and insulin levels in TALLYHO/JngJ mice. (2nd January 2016) - Nascimento, Nara F.; Hicks, Jasmin A.; Carlson, Karen N.; Hatzidis, Aikaterini; Amaral, Danielle N.; Logan, Ryan W.; Seggio, Joseph A.
ABSTRACT: Studies have shown a relationship between circadian rhythm disruptions and type-2 diabetes. This investigation examined the effects of circadian disruption (6-h phase advances) on the progression of diabetes in a type-2 diabetic mouse model –TALLYHO/JngJ – and whether wheel-running can alleviate the effects of the phase advances. 6-h advances alter fasting glucose, glucose tolerance and insulin production. Wheel-running reduced body mass, improved glucose tolerance and reduced insulin in TALLYHO/JngJ and alleviated some of the changes in diabetic symptoms due to 6-h advances. These results indicate that individuals with type-2 diabetes can benefit from physical activity and exercise can be a countermeasure to offset the effects of an acute phase advance.